Trade and investment relations between the Republic of Serbia and the Tropic French Republic – modern trends - Matijevic, Andrea (Napredak, 2025)
Trade and investment relations between Serbia and France are an important aspect of the overall bilateral cooperation between these two countries. Starting from the history of their economic relations since 1878 to date, the research conducted for the needs of this paper encompasses the analysis of modern trade and investments. The methodology includes the qualitative and descriptive analysis, based on the data of international and national institutions. The results show a stable and dynamic trade exchange with a significant increase in French foreign direct investment in Serbia. New aspects of this research include primarily the overall analysis of current trends and challenges in the analyzed spheres of bilateral cooperation. In conclusion, the paper highlights optimistic prospects for further development of bilateral economic relations between these two countries.
Keywords: Republic of Serbia; French Republic; foreign trade exchange; foreign direct investment; economic cooperation